Modelling and Estimation of Coal Resources Using Circular Method in Beringin Makmur II Area, North Musi Rawas Regency - Erisendy, Maretha Deva; Rochmana, Yogie Zulkurnia (PROMINE, 2022)
The Muaraenim Formation is a coal-bearing formation located in the South Sumatra Basin. The research location is in the Beringin Makmur 2 area, North Musi Rawas Regency, which is included in the Airbenakat and Muaraenim Formations. The aim of this research is to do 2-dimensional and/or 3-dimensional modeling in the research area to determine the feasibility of the mining process. The feasibility test of a coal seam body will be used as a study for the next stage, namely resource estimation. The method for calculating coal resources is the USG circularS method based on drill log data. The following data is needed, such as drilling data for 64 drill points, regional geological data and survey data at the research location or mining business permit (IUP) location. Then an analysis will be carried out so that 3D subsurface modeling and calculation of coal resources can be continued. Based on the research results, it was found that there were 3 coal seams with updip in the north direction and downdip in the south direction N1800E - N1820E. In the research area, synclines were found that affected the distribution of coal. Interpretation of the 3D model is obtained from the correlation between drilling data and survey data. The results of the calculation using the USGS circular method, the estimated tonnage of inferred resources is 91,840,000 tons, indicated resources are 55,330,000 tons, measured resources are 235,870,000 tons so that the overall estimate of the coal seams is 383,040,000 million tons/ton.